Irena Sendler. A nurse example of love of freedom - Pulgarin Bilvao, Lissette Paola (Investigación y Educación en Enfermería, 2012)
<!-- [if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]--> This article summarizes the life of Polish nurse, Irena Sendler, who during the Second World War helped in the escape of over 2500 Jewish children, held in the Warsaw ghetto. In spite of having been arrested by the Gestapo, she never revealed the names or whereabouts of the children she saved. Irena reminds us that nursing is the art of protecting the lives of others.